2012
DOI: 10.1038/jcbfm.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Ménage à Trois: The Role of Neurotransmitters in the Energy Metabolism of Astrocytes, Glutamatergic, and GABAergic Neurons

Abstract: This work is a computational study based on a new detailed metabolic network model comprising well-mixed compartments representing separate cytosol and mitochondria of astrocytes, glutamatergic and gamma aminobutyric acid (GABA)ergic neurons, communicating through an extracellular space compartment and fed by arterial blood flow. Our steady-state analysis assumes statistical mass balance of both carbons and amino groups. The study is based on Bayesian flux balance analysis, which uses Markov chain Monte Carlo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
5
20
0
1
Order By: Relevance
“…Estimating that each completely oxidized molecule of glucose produces 30–38 ATP molecules, depending on details included, we may conclude that the total cost for maintaining each unit of glutamate flux corresponds to 21–26 units of ATP converted to ADP + Pi (no GABAergic activity), and 6–8 units of ATP for maintaining one unit of GABA flux (no glutamatergic activity). As demonstrated in Calvetti and Somersalo (8), in spite of its coarseness, in simulations these flux estimates yield an energetic cost that correspond well to the data reported in Sibson et al (33). …”
Section: The Pathway Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…Estimating that each completely oxidized molecule of glucose produces 30–38 ATP molecules, depending on details included, we may conclude that the total cost for maintaining each unit of glutamate flux corresponds to 21–26 units of ATP converted to ADP + Pi (no GABAergic activity), and 6–8 units of ATP for maintaining one unit of GABA flux (no glutamatergic activity). As demonstrated in Calvetti and Somersalo (8), in spite of its coarseness, in simulations these flux estimates yield an energetic cost that correspond well to the data reported in Sibson et al (33). …”
Section: The Pathway Modelsupporting
confidence: 84%
“…To counterbalance the underestimate, our model enables the cells to use energy for unspecified activities by including an ATP hydrolysis in each cell. As pointed out in Calvetti and Somersalo (8), the activity level of this flux, in particular in astrocytes, can be significantly elevated. Details will be given later when the computed examples are described.…”
Section: The Pathway Modelmentioning
confidence: 69%
See 1 more Smart Citation
“…Glutamate can be converted to α-ketoglutarate by amino transferases that are found in the cytosol or mitochondria (Spanaki and Plaitakis, 2012) or by glutamate dehydrogenase that is restricted to mitochondria (Aoki et al, 1987). Although modeling studies suggest that cytosolic conversion of glutamate to α-ketoglutarate is not likely (Calvetti and Somersalo, 2012), the mitochondrial transporter that exchanges cytosolic α-ketoglutarate for mitochondrial malate (Slc25a11) was identified in the GLT-1 proteome (Genda et al, 2011). In 1982, Yu and his colleagues found that the flux of glutamate into the tricarboxylic acid cycle was about 50% greater than the flux into glutamine in astrocyte cultures (Yu et al, 1982).…”
Section: Implications For Glutamate Metabolismmentioning
confidence: 99%
“…In the opposite direction, anaplerotic reactions replenish the TCA cycle intermediates to maintain the function of the mitochondrial cycle. Cytosolic ME1 activity has an essential role in replenishing the TCA cycle in astrocytes, sustaining the pyruvate recycling activity (McKenna et al, 1995;Calvetti and Somersalo, 2012), and Nrf2-dependent activation of ME1 may be important to maintain the TCA cycle in astrocytes enabling neurotransmitter synthesis and recycling. It is also noteworthy that the impaired substrate availability caused by the lack of Nrf2 in glioneuronal cultures from Nrf2 KO mice was responsible for the increased mitochondrial ROS production found in this model (Kovac et al, 2015).…”
Section: Nrf2 Mitochondrial Bioenergetics and Neurodegenerative Disomentioning
confidence: 99%